Pengaruh Ekstrak Etanol Daun Karanda (Carissa carandas L.) Terhadap Histopatologi Ginjal Tikus Putih (Rattus norvegicus) yang Diinduksi Aloksan - Sirait, Ilhammudin; Febriani, Husnarika; -, Syukriah (Jurnal Farmasi Udayana; Vol. 12, No 1, Tahun 2023, 2023)
A metabolic condition called diabetes mellitus (DM) results from an inability to secrete insulin. The purpose of this study is to determine the impact of ethanol extract from karanda leaves (Carissa carandas L.) on diabetes mellitus mouse kidney morphology and renal histology. The study employed a complete random design (RAL) with the partition of variants into 6 groups, including normal control, negative control, glibenklamid group, and P1: karanda leaf extract doses of 500 mg/kg BB, 750 mg/kg BB, and 1000 mg/kg BB. hematoxylin-eosin (HE) staining and the paraffin method for producing mouse kidney histopathology preparations. Data analysis using the one-way Anova and the sophisticated tests of Duncan. The outcomes demonstrated that the kidneys of diabetic mice in the control and treatment groups had significantly different morphologies and histopathologies. The glomerulus was edematous in diabetic kidneys with melitus, and cell damage manifested as hydropic degeneration, necrosis of the proximal tubules, and variations in glomerular diameter. The administration of ethanol-extracted from karanda leaves can help with glomerular edema, shape, and cell healing in the proximal tubules. Conclusion: Caranda leaf ethanol extract improves the morphology, renal histology, and glomerular diameter of mice (Rattus norvegicus) with diabetic mellitus, with 1000 mg/kgbb of extract being the most efficacious dose. Keywords: Diabetes Mellitus, Karanda Leaf (Carissa carandas L.) and Kidneys